Neurodivergenta släktskap: Från representation till resonans och världsskapande - Bergenmar, Jenny (K&K - Kultur og Klasse, 2025)
This article examines how neurodivergent experience and identity are articulated in relation to history, a history where there are no obvious predecessors. Although neuropsychiatric diagnoses are contemporary constructs, neurodivergence can be used as a transhistorical concept that captures deviations from a norm in terms of perception, sociality, emotionality, and cognition. But what do neurodivergent authors themselves perceive as neurodivergence avant la lettre? The article discusses the strategies autistic authors use to establish connections with figures from the past as well as with historical literature. This is often a prominent feature in autistic memoirs, such as Joanne Limburg’s Letters to My Weird Sisters (2021) and Clara Törnvall’s Autisterna – om kvinnor på spektrat (2021). Drawing on James McGrath’s critique of autistic representation in Naming Adult Autism (2017), the article argues that resonance with texts lacking explicit representation creates opportunities for creative points of connection to history. Furthermore, the article contends that concepts from queer and trans theory, which have engaged with similar questions about how to construct a history based on marginalized experiences, can be adapted and repurposed to illuminate the strategies employed by these authors in their creation of neurodivergent genealogies and neurodivergent worldmaking.